Artificial acceleration of mammalian cell reprogramming by bacterial proteins. (4th August 2017) - Ikeda, Takashi; Uchiyama, Ikuo; Iwasaki, Mio; Sasaki, Tetsuhiko; Nakagawa, Masato; Okita, Keisuke; Masui, Shinji
Abstract : The molecular mechanisms of cell reprogramming and differentiation involve various signaling factors. Small molecule compounds have been identified to artificially influence these factors through interacting cellular proteins. Although such small molecule compounds are useful to enhance reprogramming and differentiation and to show the mechanisms that underlie these events, the screening usually requires a large number of compounds to identify only a very small number of hits (e.g., one hit among several tens of thousands of compounds). Here, we show a proof of concept that xenospecific gene products can affect the efficiency of cell reprogramming to pluripotency. Thirty genes specific for the bacterium Wolbachia pipientis were forcibly expressed individually along with reprogramming factors ( Oct4, Sox2, Klf4 and c‐Myc ) that can generate induced pluripotent stem cells in mammalian cells, and eight were found to affect the reprogramming efficiency either positively or negatively (hit rate 26.7%). Mechanistic analysis suggested one of these proteins interacted with cytoskeleton to promote reprogramming. Our results raise the possibility that xenospecific gene products provide an alternative way to study the regulatory mechanism of cell identity. Abstract : Screening of Wolbachia ‐specific proteins identified several proteins that affected mammalian cell reprogramming to pluripotency. Our results suggest that screenings of xenospecific gene products could be useful for studies on mechanisms of cell identity regulation as well as development of technologies controlling it.